Burnout and Resilience in Psychiatric Hospital Care-givers: A Cross-Sectional Study Using Mediation and Path Analyses - William Jacobowitz, (Public Health, 2025)
Background The role of resilience in mediating burnout in psychiatric hospital care-givers has not been well established in the published research. This study attempted to identify the salient factors associated with the development of burnout, specifically resilience, through a secondary analysis of data collected in a study of post-traumatic stress symptoms in a sample of hospital employees. MethodsAn analysis of data collected in a correlational study with a convenience sample of 149 care-givers in a psychiatric hospital was performed, comparing the rate of traumatic events (TEs), resilience, confidence, PTSD symptoms (PTSS), secondary traumatic stress, compassion satisfaction, and life events to burnout. The analysis employed multiple linear regression, mediation analysis and path analysis. ResultsIt was observed that episodes of trauma stress, resilience and compassion satisfaction, combined, robustly predict burnout (explained variance=65%), but that each variable is a weak predictor. In addition, resilience was not related to trauma and stress and did not mediate burnout. This finding presents a paradigm suggesting that there may be two distinctly separate pathways affecting burnout, one involving traumatic stress and the other–resilience and compassion satisfaction. ConclusionThe effect of resilience in the development of burnout may be limited to its relationship to role satisfaction (compassion satisfaction) and unrelated to traumatic stress.